Nurses’ Roles in Reducing Stigma Toward People Living with HIV-AIDS Through a Culturally Grounded Karo Spiritual Intervention Model - Sinulingga, Elysabeth; Siswadi, Yakobus; Watania, Lani Natalia (Gaceta Médica de Caracas, 2026)
Introduction: The phenomenon of caring for patients with HIV presents a unique challenge, especially for nurses working in hospital settings. Professional support is essential in the prevention, transmission control, care, and stigma reduction for people living with HIV/AIDS (PLWHA), as this condition is often complex for others to accept. This study aims to examine the role of nurses in reducing stigma toward PLWHA through a culturally sensitive spiritual intervention model based on Karo traditions.